1990
DOI: 10.1177/0146167290162009
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Counterfactual Thinking in Judgments of Affect

Abstract: The role of counterfactuals in judgments of affective reactions to outcomes was examined. Subjects read about individuals who experienced gains or losses as a result of either deciding to take action and make a change or deciding not to take any new action. In addition, the salience of the counterfactual alternative was manipulated. Past results were replicated in the case of negative outcomes: Individuals who lost money on the basis of action were judged as feeling worse than those who lost money on the basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
214
1
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 218 publications
(224 citation statements)
references
References 13 publications
7
214
1
2
Order By: Relevance
“…This "action effect" has been replicated many times and for both negative and positive outcomes in many cases using modifications of Kahneman and Tversky"s (1982) switch/stay scenario Connolly,Ordonez & Coughlan,1997;Ritov & Baron, 1995;Gleicher, Kost, Baker, Stratham, Richman & Sherman, 1990;Landman, 1987;. It has also been shown to be sensitive to a number of manipulations and can depend on such things as whether an action is consistent with a person"s personal orientation (Seta, McElroy & Seta, 2001) ,whether information about prior (Zeelenberg, van der Bos, van Dijk, & Pieters, 2002) or alternative (Ritov & Baron, 1995) outcomes is available to the decision-maker, whether an outcome is seen as reversible (Abendroth & Diehl, 2006), and whether the decisions being judged are presented in a within-or between-subjects design (N"gbala & Branscombe, 1997;Zhang, Walsh & Bonnefon, 2005).…”
Section: Agency and Counterfactual Thinkingmentioning
confidence: 89%
See 2 more Smart Citations
“…This "action effect" has been replicated many times and for both negative and positive outcomes in many cases using modifications of Kahneman and Tversky"s (1982) switch/stay scenario Connolly,Ordonez & Coughlan,1997;Ritov & Baron, 1995;Gleicher, Kost, Baker, Stratham, Richman & Sherman, 1990;Landman, 1987;. It has also been shown to be sensitive to a number of manipulations and can depend on such things as whether an action is consistent with a person"s personal orientation (Seta, McElroy & Seta, 2001) ,whether information about prior (Zeelenberg, van der Bos, van Dijk, & Pieters, 2002) or alternative (Ritov & Baron, 1995) outcomes is available to the decision-maker, whether an outcome is seen as reversible (Abendroth & Diehl, 2006), and whether the decisions being judged are presented in a within-or between-subjects design (N"gbala & Branscombe, 1997;Zhang, Walsh & Bonnefon, 2005).…”
Section: Agency and Counterfactual Thinkingmentioning
confidence: 89%
“…produces experiences of disappointment and regret (Bell, 1982;Kahneman & Tversky, 1982;Landman, 1987; as well as guilt and shame (Mandel, 2003;Niedenthal, Tangney & Gavanski, 1994), whereas a downwards counterfactual where a worse outcome is imagined produces relief or rejoicing (Gleicher, Kost, Baker, Stratham, Richman & Sherman, 1990;Guttentag & Ferrel, 2004;Landman, 1987;Loomes & Sugden, 1982). Counterfactuals are more spontaneously evoked by negative than by positive outcomes (Boniger, Gleicher & Stratham, 1994;Gleicher et al, 1990;Kahneman & Miller, 1986;Landman, 1987;Roese & Hur, 1997) though this is not always the case (Markman, Gavanski, Sherman & McMullen, 1993;Roese & Olson, 1993a,b;.…”
Section: Decisions and Regret As A Counterfactual Emotionmentioning
confidence: 99%
See 1 more Smart Citation
“…One significant issue in counterfactual thinking is that upward counterfactual thought often results in a high level of negative emotions because such thoughts focus on imagined outcomes that are better than the outcome actually obtained (Gleicher et al, 1990;McConnell et al, 2000;Roese, 1997). Negative emotions resulting from upward counterfactual thoughts can affect decision making in the future (Roese, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that upward counterfactual thinking leads to negative emotions (Boninger et al, 1994;Gleicher et al, 1990;Kahneman & Miller, 1986;Roese, 1994). In particular, recent studies have found that regret and disappointment are two critical, different types of negative emotions in response to counterfactual thoughts, and they are directly related to decision making (Inman et al, 1997;Marcatto & Ferrante, 2008;Zeelenberg et al, 1998b;Zeelenberg & Pieters, 1999;Zeelenberg et al, 2000).…”
Section: Study 2: Pre-counterfactual Thinking and Anticipated Emotionsmentioning
confidence: 99%